EFFECTIVE STRESS FINITE ELEMENT ANALYSIS OF PILE-SOIL INTERACTION PROBLEMS (Journal of Engineering, 2007)
The effective stress method is developed to predict the axial capacity of piles in clay. Thismethod is based on the principle that, at failure, the available shear resistance at the pile soilinterface is related to the mean normal effective stress at the pile face and the effective stressfriction angle for the soil sliding on the pile material.In this paper, the coupled non-linear finite element method is used to analyze some pile-soilinteraction problems. This computer program ( CRISP ) is used for this task. Eight- nodeisoparametric elements were used for displacements while four- node elements are used forpore pressure. Interface elements are used to simulate the interaction between the pile and thesoil. The soil is assumed to follow different models, linear elastic and modified Cam-claymodel. A comparison is made between the measured and predicted settlements and excesspore water pressures and good convergence was obtained in which the proposed techniqueused in this paper, in which the measured excess pore water pressures are considered as initialpore pressures in the computer program ( CRISP ). No load was applied on the pile. Thedissipation of excess pore water was studied through carrying out consolidation analysis.